Geographic Information System Mapping of Housing Locations Using Web-Based Breadth First Search Algorithm - Arif Arizal; M Mahaputra Putra; Dwi Budi Marwanto (Fakultas Teknik Universitas Bhayangkara, 2020)
Sidoarjo Regency as one of the cities with an increasingly dense population and the needs of people who want to find information about housing quickly, makes a Geographical Information System indispensable, especially in terms of finding housing locations. Therefore, the authors create a web-based housing geographic information system in Sidoarjo Regency using Breadth First Search to design the system interface and logic, MySQL for database system design and Bing Api for mapping. Information presented in the form of housing names, addresses, photos of housing, pictures of house types, house plans, availability and prices of each type of house. With the GIS (Geographical Information System), it is hoped that the public can more easily and quickly get housing information in Sidoarjo Regency. The results of this study show the details of the housing location from the user's location according to the radius to be selected and know the approximate distance of travel time to the residential location